Genetic Analysis Reveals Complete Androgen Insensitivity Syndrome in Female Children Surgically Treated for Inguinal Hernia - Nurin A. Listyasari; Gorjana Robevska; Ardy Santosa; Aurore Bouty; AZ Juniarto; Jocelyn van den Bergen; Katie L. Ayers; Andrew H. Sinclair; Sultana MH Faradz (Journal of Investigative Surgery, 2021)
Background: Complete androgen insensitivity syndrome (CAIS) is a congenital condition caused by genetic defects in the androgen receptor (AR) gene located on the X chromosome, which lead to a phenotypical female individual with a 46, XY karyotype. Early diagnosis of CAIS is essential for proper clinical management, allows assessment of familial risk and contributes to healthcare decisions. However, diagnosis of CAIS can be overlooked in girls with inguinal hernia, resulting in inappropriate management. Methods: Five female patients from three unrelated families presented to our genetic clinic with primary amenorrhea. Each patient had been diagnosed with inguinal hernia in childhood and had undergone hernia repair without further investigation into what was contained in the hernial sac. We carried out physical examination, cytogenetic studies, hormonal evaluation, and molecular analysis to establish a comprehensive diagnosis. Family history and pedigree were collated to identify at-risk family members. Results: All patients presented with female external genitalia. Cytogenetic studies revealed a 46, XY karyotype and hormonal analysis suggested a diagnosis of CAIS. Sequencing of the AR gene in all patients and suspected family members revealed pathogenic variants in the AR gene and confirmed the molecular diagnosis of CAIS. Conclusions: We report the delayed diagnosis of CAIS in female Indonesian patients with a history of inguinal hernia in childhood. An early diagnosis of CAIS is essential for appropriate clinical management, as well as assessing familial risk. Increasing awareness among clinicians is paramount, and we encourage a CAIS diagnosis to be considered in any patient presenting with female appearance and inguinal hernia.